The Loss of a Clan: Abandoning Ethos of the East African Revival by the Contemporary Kenyan Christian - Mwangi, Perminus Mburu; Pam, Gyang David; Nkansah-Obrempong, James (European Scientific Journal, ESJ, 2022)
This study investigated two practises of the East African Revival (EAR) movement; the public testimony of one’s salvation and the public confession of all known sins. The study further sought to know the attitude of the contemporary Christian on the same. The study was qualitative in strategy with a phenomenological design. Criterion based purposive sampling was used to select the participants. The tools for gathering data were In-depth interviews, Focus Group Discussions, and Document Review. Thematic Coding Analysis was used to analyse the data. The EDNA model for practical theology was applied as the theological framework. Findings show that the EAR members held the public testimony and public confession of sin as foundational to their doctrine and practice. The two practices helped them to create a unique identity and cohesiveness, after separating from their familial clans at conversion, hence forming a new spiritual clan of their own. The contemporary Christian on the other hand finds these two tenets of the EAR, intrusive and unacceptable. With no alternative ways of building cohesiveness and a unique identity, the younger believers are left without a clan hence becoming spiritual orphans. Traditional Anglicanism, with its focus on sacraments and liturgy, and African Traditional Religions are among the formations fighting to adopt these spiritual orphans. The study recommends that the church and society revisit these practices and apply them appropriately in the fight against corruption and tribalism, among other ills in Kenyan society.